Epidemiological investigation of porcine circovirus type 2 and its coinfection rate in Shandong province in China from 2015 to 2018 - Zicheng Ma; Mengda Liu; Zhaohu Liu; Fanliang Meng; Hongyu Wang; Longlong Cao; Yan Li; Qiulin Jiao; Zifeng Han; Sidang Liu (BMC Veterinary Research, 2021)
Abstract Background Porcine circovirus type 2 (PCV2) is one of the crucial swine viral pathogens, caused porcine circovirus associated diseases (PCVAD). Shandong province is one of the most important pork producing areas and bears a considerable economic loss due to PCVAD. However, there is limited information on epidemiology and coinfection rate of PCV2 with other critical swine diseases in this area, such as porcine reproductive and respiratory syndrome virus (PRRSV), classical swine fever virus (CSFV), Pseudorabies virus (PRV), and porcine epidemic diarrhea virus (PEDV). Results Overall, 89.59% serum samples and 36.98% tissue samples were positive for PCV2 specified ELISA and PCR positive for PCV2, respectively. The coinfection rates of PCV2 with PRRSV, PRV, CSFV, and PEDV were 26.73%, 18.37%, 13.06%, and 3.47%, respectively. Moreover, genetic characteristic of PCV2 were analyzed based on the cap genes showing that PCV2d is the dominant sub-genotype circulating in the province. Conclusions Our findings reveal that PCV2d, as the dominant strain, is prevailing in pig farms in Shandong province at high levels. There was a high frequency of coinfection of PCV2 and PRRSV.